A Common Toxicologic Emergency: Caustic and Corrosive Ingestions in Children Presenting to the Emergency Department - Gamze Gökalp; Emel Berksoy; Murat Anıl; Mustafa Onur Öztan (Journal of Pediatric Emergency and Intensive Care Medicine, 2020)

(untitled)
Introduction:Accidental ingestion of cleaning substances poses a risk to children all over the world and in our country. In this study, we aimed to investigate the causes of this condition and the clinical problems caused by such serious consequences.Methods:This study was designed as an observational, descriptive, retrospective study. The data were obtained from the hospital electronic medical records. In addition to the demographics, the type of poisoning, presenting complaints, diagnostic tests, medications, treatments and outcomes (results of esophagoscopy and follow-up) were also investigated. The cases were divided into two groups: patients who underwent esophagoscopy and were kept under observation and those kept under observation without esophagoscopy. Patients who underwent esophagoscopy were further divided into two groups as ‘histopathological examination with normal findings ' and ‘histopathological examination with abnormal findings. Hemogram, biochemical parameters and C-reactive protein levels were recorded. The cases with missing or inaccessible data were excluded from the study. The study was approved by the local ethics committee. The SPSS 22.0 program was used for the analysis of the data.Results:Four thousand three hundred forty five had a diagnosis of poisoning and 295 were exposed to corrosive substances. The most common poisoning agent was bleach (23.7%). Of the patients, 132 (57.9%) underwent only clinical follow-up and 96 (42.1%) underwent esophagoscopy with clinical follow-up. The occurrence rate of esophageal strictures was significantly higher in patients ingesting degreasers (p<0.05). There was a significant relationship between elevated platelet count and amylase level and presence of esophageal pathologies (p<0.05).Conclusion:Exposure to corrosive substances is a common problem during childhood. It was observed that ingestion of degreasers increased the risk of esophageal stricture formation. Elevated platelet count and amylase level were found to be predictive of esophageal injury.